Vascular endothelial growth factor (VEGF) is increased in serum, but not in cerebrospinal fluid in HIV associated CNS diseases. Issue 2 (23rd January 2004) - Sporer, B; Koedel, U; Paul, R; Eberle, J; Arendt, G; Pfister, H-W
Abstract : Vascular endothelial growth factor (VEGF) is a potent angiogenic and mitogenic peptide, which also induces several mediators that may play a role in HIV induced CNS damage. VEGF levels were determined in cerebrospinal fluid (CSF) and serum samples from patients with (n = 8) and without (n = 19) directly HIV associated CNS disorders and HIV negative control patients (n = 18). VEGF serum but not CSF levels were significantly increased in HIV infected patients with (381.1 (78.9) pg/ml) HIV associated CNS diseases compared with those without (120.8 (13.1) pg/ml) and HIV negative control patients (133.1(14.8) pg/ml). Serum samples from patients with untreated HIV associated encephalopathy (HIVE, n = 3) contained the highest VEGF levels (583.9 (71.5) pg/ml). In two patients VEGF serum levels were reduced during antiretroviral therapy. However, regardless of effective viral suppression, patients with HIVE still had higher levels compared with HIV infected patients without HIVE. A relevant increase of serum VEGF was not observed in patients without HIVE though high HI viral load. We conclude that HIVE is associated with increased serum VEGF levels. Further studies are warranted to elucidate the role of VEGF in HIVE.